Karakteristik Morfologi Pohon Terpilih Sebagai Entris Tanaman Alpukat (Persea americana Mill) - Kiani Hamid; Rima Melati; Zauzah Abdullatif; Sofyan Samad; Abdul Rahmat Mandea; Sartika Syafie (Universitas Khairun, 2026)
Avocado (Persea americana Mill.) is a tropical fruit plant with high economic value and is generally propagated vegetatively through grafting techniques using scions. The success of propagation and the quality of the resulting plants are largely determined by the characteristics of the tree selected as the scion source. The purpose of this study is to describe the morphological characteristics of avocado mother trees that need to be considered in the selection of scion sources through observation and systematic literature studies from various publications. The morphological study was based on observations of mother trees in Tubo Village and analyzed descriptively by tabulating quantitative data. The results of the study indicate that the ideal tree selected as a scion source must meet morphological criteria in the stem, leaves, branches, and visual health of the plant. The tree trunk shows vigorous growth with balanced branching. The leaves have a distinctive shape, size, and color according to the variety and are free from pathogen symptoms. Branches used as scion sources are young branches with a diameter of 0.5-1 cm, have undergone complete growth, have healthy buds, and come from parts of the plant with high productivity. Selection of mother trees based on appropriate morphological characteristics is the first step in providing quality scions to ensure the success of avocado propagation and productivity.